Feedback Control in a Periodic Delay Single-Species Difference System - Yi Yang; Zhijun Liu (Discrete Dynamics in Nature and Society)
A periodic delay single-species difference system with feedback control is established. With the help of analysis method and Lyapunov function, a good understanding of the permanence and global attractivity of the system is gained. Numerical simulations are presented to verify the validity of the proposed criteria. Our results show that feedback control has no influence on the permanence while it has influence on the global attractivity of the system.